2012
DOI: 10.1016/j.clinph.2011.06.027
|View full text |Cite
|
Sign up to set email alerts
|

EEG correlates of fatigue during administration of a neuropsychological test battery

Abstract: Objective Mental fatigue, a poorly understood symptom of sports-related concussion, ideally requires assessment across multiple modalities. Our study aimed to examine mental fatigue effects among ten neurologically normal, athletically active students undergoing typical concussion testing. It is our intention to ultimately address the question whether fatigue effects due to mild traumatic brain injury (mTBI) may become confounded with fatigue effects due to testing effort. Methods Fourteen athletically activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
63
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 48 publications
13
63
1
1
Order By: Relevance
“…This finding is consistent with the results of the previous studies, in which fatigue was caused by performing a monotonous simulation driving task [24] or Stroop neuropsychological test [25] for 90 min without any break: In these studies, the theta power density on the frontal EEG electrode site was increased after the mental fatigue-inducing task trials. It has been reported that the theta power density is positively related to sleepiness [26,27].…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with the results of the previous studies, in which fatigue was caused by performing a monotonous simulation driving task [24] or Stroop neuropsychological test [25] for 90 min without any break: In these studies, the theta power density on the frontal EEG electrode site was increased after the mental fatigue-inducing task trials. It has been reported that the theta power density is positively related to sleepiness [26,27].…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with previous research implicating theta-band oscillations in neurocognitive deficits (Wichniak et al, 2014) or cognitive fatigue (Barwick et al, 2012) in general, and in mnemonic operations in particular: Successful memory encoding has been associated with changes in theta-band oscillatory power along a specific time course (Guderian et al, 2009;Long et al, 2014;Osipova et al, 2006;Sederberg et al, 2006), and theta-band oscillations are sensitive to factors affecting memory performance such as processing depth, contextual manipulations and cognitive load (Guderian et al, 2009;Hanslmayr and Staudigl, 2014;Sederberg et al, 2006). Moreover, it has been suggested that mnemonic operations might be dependent on precise modulations of theta-band synchronization within widely distributed brain networks (Burke et al, 2013;Fell and Axmacher, 2011;Sato and Yamaguchi, 2007;Summerfield and Mangels, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…The greater elicited attention and cognitive engagement rather suggests that the experimental task was more mentally demanding. EEG measures that have repeatedly been associated with the occurrence of mental fatigue are increases in frontal and in frontal, central and parietal -power [47,48,8,49]. Moreover, if one considers the continuous change of a measure as a criterion in order to assign it to the development of mental fatigue, the increase in frontal power seems to be the most valid measure of mental fatigue according to the data reported by Wascher et al [8] and Trejo et al [49].…”
Section: Mental Fatigue Inducing Interventionsmentioning
confidence: 71%